Prospects of using organic Rankine cycle for geothermal power generation - Tulenbayev, Zhanat; Zhanpeisova, Aizhan; Omarova, Ardak; Tleshova, Akmaral; Abdlakhatova, Nazym (International Journal of Power Electronics and Drive Systems (IJPEDS), 2025)
The relevance of this study stems from the desire to develop efficient and sustainable methods of energy extraction from low-temperature geothermal resources, which is of key importance in the context of finding alternative energy sources and reducing dependence on conventional, often non-renewable sources. The purpose of this study was to analyze the organic Rankine cycle (ORC) to improve the efficiency of energy recovery from low-temperature geothermal sources. The present study employed the analytical method, the deduction method, the induction method, the functional method, the classification method, the synthesis method. ORC applications for geothermal energy were comprehensively analyzed, with a focus on the investigation of low-temperature resources. The best cycle performance parameters were determined, considering diverse operating conditions. Concrete technical recommendations were developed for the selection of organic working media to improve system efficiency. The summarized findings highlight the potential of the ORC in enhancing the sustainability and efficiency of geothermal systems.